The influence of tree induce suction on soil suction profiles - Mohd Fakhrurrazi, Ishak; Nazriali, Ali; Azmin, Kassim (eSAT Publishing House Pvt. Ltd., 2013)
This study provided an investigation of active root tree zone located at the toe of the slope. This section of slope generated suction due to tree water uptake during dry season. A field monitoring set up program was carried out to collect matric suction data at slope with absent of a tree and with a tree located at toe of the slope. The installations of Jet-fill tensiometer and Gypsum blocks to measured matric suction were placed at vicinity of tree with certain depths and distances. The distribution in matric suction values and matric suction profiles responses to tree water uptake and rainfall were investigated. The decreased of soil matric suction after intense rainfall in this monitoring period as a function of an initial condition before the water uptake driven by active root tree substantially increased matric suction (low moisture content). Matric suction significantly increased at vicinity of tree trunk located at toe of slope compared to the slope without tree. This exploration provides the viewed of mature tree can significantly alter the suction distribution driven by transpiration in an unsaturated soil slope. It takes consideration by preserved mature tree can improved soil properties in geotechnical slope design.